2013
DOI: 10.2174/2211536611302010004
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs in Bone Diseases

Abstract: MicroRNAs (miRNAs), which mainly inhibit protein expression by targeting the 3'UTR (untranslated region) of mRNAs, are known to play various roles in the pathogenesis of many different types of diseases. Specifically, in bone diseases, recent emphasis has been placed on the involvement of miRNAs in the differentiation and proliferation of bone and cartilage cells, particularly with regards to how these mechanisms contribute to bone homeostasis. In this review, we summarize miRNAs that are important in the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Previous studies have demonstrated that miRNAs played an important role in the development of osteoporosis [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that miRNAs played an important role in the development of osteoporosis [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested the regulatory functions of miRNAs in periodontitis involved in bone remodeling (Yan et al, 2017). Recent experimental reports have demonstrated that miRNAs participate in every step of bone formation and bone homeostasis from embryonic bone development to adult bone tissue maintenance by regulating the differentiation, growth, and activity of different cell systems inside and outside the skeleton (Moore & Xiao, 2013). The miRNAs have been shown to regulate cell proliferation and may be related to directed differentiation (Chen et al, 2014;Huang, Geng, Wei, Zhang, & Jiang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that alterations in miRNA expression are strongly linked to various kinds of human diseases, including cancers (Adams et al , ), cardiovascular diseases (Latronico and Condorelli, ), inflammatory and autoimmune diseases (Zeng et al , ), and musculoskeletal disorders (Lian et al , ; Moore and Xiao, ). It has been reported that miRNAs have stable property and tissue‐specificity, and might therefore be used as biomarkers for blood‐based diagnosis of diseases (Chen et al , ; Mitchell et al , ).…”
Section: Perspectivesmentioning
confidence: 99%
“…MicroRNAs (MiRNAs) are a type of small non‐coding RNA molecule of 20–22 nucleotides in length, which play important roles in a number of physiological processes, such as individual development (Ying et al , ), organ formation (Joglekar et al , ; Khoshgoo et al , ), tumorigenesis (Lawrie, ; Papaconstantinou et al , ; Zhan et al , ), and cell proliferation, differentiation and apoptosis (Luo et al , ; Mathieu and Ruohola‐Baker, ). Due to the prominent and extensive functions of the miRNA, the miRNA dysexpression or the combinational alteration between miRNA and its target genes will contribute to certain diseases, such as cancer (Tilghman et al , ), autoimmune diseases (Buckland, ) and bone‐related diseases (Moore and Xiao, ). Interestingly, some miRNAs, such as miR‐155 (Wang et al , ), miR‐146a (Zhao et al , ) and miR‐377 (Tsirimonaki et al , ), are present in intervertebral disc (IVD), and their dysregulation in IDD might serve as potential biomarkers for the early diagnosis of IDD.…”
Section: Introductionmentioning
confidence: 99%